Propylene/propane separation by vacuum swing adsorption using 13X zeolite - Silva, Francisco A. Da; Rodrigues, Alírio E. (AIChE journal, 2001)
A vacuum swing adsorption process using 13X zeolite pellets with five steps was designed to split an equimolar mixture of propylene/propane: pressurization with feed; high‐pressure feed; high‐pressure purge with product; cocurrent blowdown; and counter‐current vacuum blowdown, where the enriched propylene product is withdrawn. In the process, the partial pressure of the C3‐mixture is controlled with nitrogen, which is used as inert gas. With an equimolar feed of C3 diluted to 50% with nitrogen, the column is fed at 5 bar and 423 K, and the product is obtained when the total pressure is lowered to 0.1 bar. After 15–20 cycles, the cyclic steady‐state condition is achieved, a propylene‐enriched stream of 98% mol relative to propylene/propane mixture, with 3.2% of nitrogen, a recovery of 19% (molar basis), and a productivity of 0.785 mol/kg·h is obtained. The experimental work was complemented with numerical simulations, and the effect of different operating parameters on the performance of the VSA was considered.